Levels of Heavy Metals in Banana, Cocoa and Oil Palm Farming Systems in Cameroon - Jetro Nkengafac, Njukeng; Kratz, Sylvia; Schnug, Ewald (International Journal of Environment, 2020)
The potential accumulation of heavy metals in soils due to rapid urban and industrial development, and increasing reliance on agrochemicals in the last several decades has been of public concern. Excessive heavy metal accumulation in soils may not only result in environmental contamination, but excessive heavy metal uptake by crops may affect food quality and safety. The heavy metal concentrations of soils in banana, cocoa and oil palm farming systems in Fako Division of the South West Region of Cameroon were studied. For soil quality assessment, soil samples were collected at two depths: 0-15 cm and 15-30 cm and analyzed for seven heavy metals (Cd, Cu, Cr, Ni, Mn, Pb and Zn) using inductively coupled plasma optical emission spectrometer (ICP-OES). Cd levels in these soils were below the limits of detection (LOD) at both depths. Average contents of Cd, Cu, Cr, Mn, Ni, Pb and Zn in mg/kg ranged in the order: Cd (< LOD) < Pb (10.7 -17.1) < Cu (59.7-112.7) < Ni (100.2 -174.5) < Zn (129.7-180.4) < Cr (192.7-685.3) < Mn (2731.5-5053.5) for both depths. The soils were all acidic (pH; 4.2-5.5). There were significant variations (p≤0.05) in Cu, Cr, Mn and Zn concentrations within  different farming system(s). The soils of the studied farming systems had heavy metal levels within the allowable limits for agriculture. However, the levels of Cu, Cr and Ni were higher in some samples. Although these soils are considered to be unpolluted, care should be taken to avoid high concentrations of heavy metals.